The role of EMMPRIN/CD147 in regulating angiogenesis in patients with psoriatic arthritis - Michal A. Rahat; Mirna Safieh; Elina Simanovich; Eliran Pasand; Tal Gazitt; Amir Haddad; Muna Elias; Devy Zisman (Arthritis Research & Therapy, 2020)
Abstract Background Angiogenesis plays a central role in the pathophysiology of rheumatic diseases. Patients with psoriatic arthritis (PsA) demonstrate increased vascularity over patients with rheumatoid arthritis (RA), with unknown mechanisms. Methods We evaluated the serum levels of several pro- and anti-angiogenic factors in 62 PsA patients with active disease, 39 PsA patients in remission, 33 active RA patients, and 33 healthy controls (HC). Additionally, we used an in vitro co-culture system of fibroblast (HT1080) and monocytic-like (MM6) cell lines, to evaluate how their interactions affect the secretion of angiogenic factors and angiogenesis promoting abilities using scratch and tube formation assays. Results PsA patients, regardless of disease activity, exhibited higher levels of EMMPRIN/CD147, IL-17, and TNF-α relative to RA patients or HC. Factors, such as IL-6, and the ratio between CD147 and thrombospondin-1, exhibited elevated levels in active PsA patients relative to PsA patients in remission. Secretion of CD147, VEGF, and MMP-9 was increased in vitro. CD147 neutralization with an antibody reduced these levels and the ability of endothelial cells to form tube-like structures or participate in wound healing. Conclusions CD147 plays a role in mediating angiogenesis in PsA, and the therapeutic possibilities of neutralizing it merit further investigation.